Effect of Stocking Density on Stress-Related Gene Expression of Pacific White Shrimp (Litopenaeus vannamei) Infected with Infectious Myonecrosis Virus (IMNV) - Nurhudah, Moch.; Baladrat, Nur Komariah; Rahardjo, Sinung; Utari, Heny Budi; Wiradana, Putu Angga (Jurnal Medik Veteriner, 2024)
The stress level of vannamei shrimp (Litopenaeus vannamei) is affected by increased density and several genes are expressed under the condition. This study aimed to determine the expression of genes encoding white shrimp stress after density treatment and the infectious myonecrosis virus (IMNV) challenge test. A completely randomized design (CRD) was carried out with 6 treatment groups, i.e. 3 different stocking density groups without IMNV infection (100, 200, and 400 shrimp/m2) and 3 different stocking density groups + IMNV infection (100, 200, and 400 shrimp/m2). In addition, a shrimp density of 400 shrimp/m2 reported the fastest rate of developing the IMNV virus as seen from the clinical symptoms. The lowest cumulative number of shrimp deaths was at a density of 100 shrimp/m2 and was caused by the IMNV virus confirmed through RT-PCR. Expression of stress-coding genes was divided into upregulated and downregulated characteristics. The upregulated genes were lectin and translationally controlled tumor protein (TCTP), while the downregulated gene was Toll Receptor. The results showed that the expression of genes related to immunity in L. vannamei was upregulated after pathogen challenges such as lectin and TCTP, meanwhile, the Toll receptor gene was downregulated. Further study should also be performed to measure the expression of the three genes in revealing the immune pathways.